Simondon and Bohm between determinism and indeterminism - Jovićević Andrej (Filozofija i Društvo, 2022)
The radical redefinition of the landscape of physics that followed the contributions of Niels Bohr and Werner Heisenberg at the start of the 20th century led to plethora [of] new perspectives on age-old metaphysical questions on determinism and the nature of reality. The main contention of this article is that the work of Gilbert Simondon - whose magnum opus possesses a scope uniting the most basic philosophical concerns with the (then) most recent breakthroughs in natural sciences - is highly relevant for an adequate understanding of the split between determinism and indeterminism, as well as the underlying presuppositions which have driven some influential contributions to this topic. To this end, the article shows that the more deterministic interpretation of quantum mechanics offered by David Bohm and Louis de Broglie proves to be a valuable reference point for a more precise use and understanding of Simondon’s transductive logic - especially when its philosophical lapses are considered closely. Finally, following the considerations of both thinkers, we aim at a more precise reconsideration of the stakes of indeterminism in modern physics, as well as a restructuration of what is often understood as a polarization.